AN ANALYSIS OF THE WRITTEN GRAMMATICAL ERRORS BY USING DESCRIPTIVE TEXT IN THE SIXTH SEMESTER STUDENTS’ AT PASIFIK UNIVERSITY OF MOROTAI - Noviyanti Hakim (Esteem Journal of English Education Study Programme, 2019)
Error Analysis is one of the major topics in the field of second language acquisition research. Error is a deviation from the adult grammar of a native speaker. Errors made by the learners may give contribution in understanding the process of second language acquisition. An error analysis has some contributions to the teaching and learning process. Writing is the most difficult one for all language users whether the language is the first, second, or foreign language, because writing is an extremely complex cognitive activity. In this study focus on the descriptive qualitative that analyze and to classify the types of students’ grammatical errors in essays descriptive paragraph. The objective are (1) What errors were identified in the students’ essays?, (2) What grammatical rules were applied to justify the corrections made?, (3) How frequent were the errors commited in the essays?. The researcher took 23 students as the samplesize. The results showed that using error analysis can be improved students’ in understanding the basic grammar rules. Improvement basic grammar rules such as subject and verb agreement, word usage, sentence fragment, verb tense, spelling, punctuation, pronouns, use of article and linking verbs, adjective. The knowledge about grammar or structure factors also have big rule in writing because a sentence will be meaningful if it is arranged in right patterns. Moreover, the students should know and understand about the basic grammar rules.